Biochemical Indicators of Implantation Success of Tissue-Engineered Oral Mucosa. (January 2015) - Kuo, S.; Zhou, Y.; Kim, H.M.; Kato, H.; Kim, R.Y.; Bayar, G.R.; Marcelo, C.L.; Kennedy, R.T.; Feinberg, S.E.
Real-time (RT) determination of the health of in vitro tissue-engineered constructs prior to grafting is essential for prediction of success of the implanted tissue-engineered graft. In addition, the US Food and Drug Administration requires specific release criteria in RT prior to the release of tissue-engineered devices for human use. In principle, assessing the viability and functionality of the cellular component can be achieved by quantifying the secretion of growth factors and chemokines of tissue-engineered constructs. Ex vivo–produced oral mucosa equivalents (EVPOMEs) were fabricated under thermally stressed conditions at 43 °C for 24 h to create a functionally compromised EVPOME. We used microchannel enzyme-linked immunosorbent assay to evaluate the functionality of the cellular component, oral keratinocytes, of stressed and unstressed EVPOMEs by measuring the release of vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), human β-defensin 1 (hBD-1), and tissue inhibitor of metalloproteinase 1 and 2 (TIMP-1 and -2) into the spent medium, which was collected on the same day prior to graft implantation into severe combined immunodeficiency mice. Implanted EVPOMEs' histology on the seventh postimplantation day was used to correlate outcomes of grafting to secreted amounts of IL-8, hBD-1, VEGF, TIMP-1, and TIMP-2 from corresponding EVPOMEs. Our findings showed that significantly higher levels of IL-8, hBD-1, and TIMP-2 were secreted from controls than from thermally stressed EVPOMEs. We also found a direct correlation between secreted VEGF and IL-8 and blood vessel counts of implanted EVPOMEs. We concluded that measuring the constitutive release of these factors can be used as noninvasive predictors of healthy tissue-engineered EVPOMEs in RT, prior to their implantation.